Uncertain Futures in Evolving Financial Markets - Anita K. Krug (Washington University Law Review, 2016)
Today’s publicly offered investment funds, including mutual funds, have ever more diverse investment strategies, as they increasingly invest in financial instruments that, in earlier years, had been the province of only the most sophisticated investors. Although the new landscape of investment possibilities may substantially benefit retail investors, one financial instrument attracting increasing amounts of retail investors’ assets is acutely troublesome: the commodity futures contract. Futures originated as a means for farmers and other producers of agricultural commodities to ensure that their products could be sold at reasonable prices. Early on, the goals of futures regulation centered on one particular risk facing futures market participants—manipulative trading that destabilizes futures markets—with little emphasis on other risks, including risks to futures traders’ assets. Over the years, that goal has remained largely static. As this Article argues, that is the problem. The many retail investors that now participate (indirectly) in the futures markets are at risk as a result of the inadequate regulation of futures commission merchants (“FCMs”), the brokerage firms that are essential for futures transactions. “Inadequate” regulation in this context, moreover, means inadequate procedural regulation—regulation aimed at protecting assets that a brokerage customer deposits with a broker for purposes of carrying out her trading activities. The weaknesses of the procedural regulation of FCMs are evident in rules governing both FCMs’ operations and the liquidation of insolvent FCMs. And the deficiencies are more than theoretical, having become all-too-evident in the wake of two recent FCM bankruptcies. Proposing tailored policymaking solutions, this Article further contends that futures regulation can become substantially more effective—and do so in a cost-effective manner that need not excessively disrupt existing regulatory approaches. These proposals would not only help protect retail investors as they navigate new investment options; they would also help fortify the promising role that futures trading has begun to play in twenty-first century financial markets.
Keywords: financial markets; futures; risk; regulation; financial regulation